Is the southern crab Halicarcinus planatus (Fabricius, 1775) the next invader of Antarctica? - Lopez-Farran, Zambra; Guillaumot, Charlene; Vargas-Chacoff, Luis; Paschke, Kurt; Duliere, Valerie; Danis, Bruno; Poulin, Elie; Saucede, Thomas; Waters, Jonathan; Gerard, Karin Francoise (My University, 2021)
The potential for biological colonization of Antarctic shores is an increasingly important topic in the context of anthropogenic warming. Successful Antarctic invasions to date have been recorded exclusively from terrestrial habitats. While non-native marine species such as crabs, mussels and tunicates have already been reported from Antarctic coasts, none have as yet established there. Among the potential marine invaders of Antarctic shallow waters is Halicarcinus planatus (Fabricius, 1775), a crab with a circum-Subantarctic distribution and substantial larval dispersal capacity. An ovigerous female of this species was found in shallow waters of Deception Island, South Shetland Islands in 2010. A combination of physiological experiments and ecological modelling was used to assess the potential niche of H. planatus and estimate its future southward boundaries under climate change scenarios. We show that H. planatus has a minimum thermal limit of 1 degrees C, and that its current distribution (assessed by sampling and niche modelling) is physiologically restricted to the Subantarctic region. While this species is presently unable to survive in Antarctica, future warming under both 'strong mitigation' and 'no mitigation' greenhouse gas emission scenarios will favour its niche expansion to the Western Antarctic Peninsula (WAP) by 2100. Future human activity also has potential to increase the probability of anthropogenic translocation of this species into Antarctic ecosystems.
Keywords: climate change; establishment; niche modelling; non-native species; reptant crab; southern ocean; survival; thermotolerance